An Analysis On The Capacity Of ISPA Personnel In Finding Pneumonia Case In Balita At Puskesmas In Medan, In 2018 - Atika Arif Siregar; Tarsayad Nugraha; Aisyah Simanjorang (JURNAL BIDANG ILMU KESEHATAN, 2019)
Abstract            Introduction: There were 7,575 cases of pneumonia suffered by balita (below 5 year-old children) in Medan in 2017, but only 349 cases which were found. Objective: The objective of the study was to find out the capacity of ISPA personnel in finding pneumonia case in balita at the Puskesmas in Medan, in 2018. Method: The study used descriptive quantitative method with cross sectional design. It was dine in September, 2018. The population was 39 ISPA personnel, and the samples were taken by using total population technique. Result: The result of chi square statistic test showed that the intellectual capacity of ISPA personnel was at p-value=0.003, their emotional capacity was at p-value=0.029, and their physical capacity was at p-value=0.001. Conclusion: There was the correlation of intellectual capacity, emotional capacity, and physical capacity of ISPA personnel with the finding of pneumonia cases in balita at the Puskesmas in Medan, in 2018.Keywords: Capacity of ISPA Personnel, Pneumonia